The patient's perspective on the symptom and everyday life impact of AL amyloidosis. (2nd October 2015) - Lin, Huamao Mark; Seldin, David; Hui, Ai-Min; Berg, Deborah; Dietrich, C. Noelle; Flood, Emuella
Abstract: Introduction : This study aimed to understand the symptomatic impact of amyloid light-chain (AL) amyloidosis from the patient's perspective. Methods : Four data sources were included: a literature review, review of online patient blogs, expert clinician interviews and patient interviews. Patients were recruited through the Amyloidosis Foundation and physician referral. Phone interviews were conducted and included open-ended concept elicitation questions. Thematic analysis was performed to identify symptoms and impacts. Descriptive statistics were used to characterize the sample. A conceptual model was developed depicting the impact of disease and treatment. Results : Two hundred seventy abstracts were identified; 10 articles were deemed relevant. No qualitative studies were identified, and only three studies included patient-reported measures. Ten patients completed interviews (mean age 61 [±8]; 7 male). Over 25 signs/symptoms were identified, including fatigue, weakness, dyspnea, neuropathy, edema, dizziness/lightheadedness, anorexia, diarrhea and constipation. Impacts included reduced physical and social functioning, and emotional impacts, including frustration, anxiety and depression. Findings from the blogs and expert interviews were consistent with patient reports. Conclusion : Symptoms can vary widely, but a core set of symptoms were common across patients. The conceptual model derived from this study can be used to ensure a patient-centered approach to drug development.